Pemanfaatan Layanan Perbankan Digital dalam Meningkatkan Kepuasan Nasabah Studi Empiris pada BMT NU Barokah Blora Cabang Randublatung - Mustain; M. Syaihul Anwari (https://journal.metanusantara.com/jenius/index.php/jem, 2025)
This research uses a qualitative case study approach; data obtained through in-depth interviews and observations of customers and managers of BMT NU Barokah Blora Randublatung Branch. The main objective of the study was to evaluate the utilisation of mobile banking services in fulfilling customers' financial transaction needs, measuring the level of user satisfaction related to convenience, security, and speed of service. The results show that the mobile banking service has been effective, with a high level of user satisfaction especially in the aspects of ease of access and transaction security. In addition, the implementation of this service is in line with sharia values and supports the sustainability of the institution. However, there is still a need to improve digital literacy among customers to maximise service utilisation. This research makes an important contribution to the development of technology-based Islamic microfinance services.